2013
DOI: 10.1371/journal.pone.0054518
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 Deficiency Exerts Protective Effect against H2O2 Induced Oxidative Stress in Isolated Cardiomyocytes

Abstract: Apart from the antihyperglycemic effects, DPP4 inhibitors and GLP-1 molecules are involved in the preservation of cardiac functions. We have demonstrated that DPP4-deficient rats possess resistance to endotoxemia and ischemia/reperfusion stress. However, whether the decrease of DPP4 activity simply augmented the GLP-1 signaling or that such decrease resulted in a change of cellular function remain unclear. Accordingly, we investigated the responses of H2O2-induced oxidative stress in adult wild-type and DPP4-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 45 publications
2
39
0
Order By: Relevance
“…In addition, we found that silence of DPP4 inhibited superoxide generation induced by HNF1b knockdown in AML-12 hepatocytes, indicating that DPP4 also involved in HNF1b knockdown-associated superoxide generation. Previous studies have reported that DPP4 inhibitors played an antioxidant role mainly through regulating expression of antioxidant enzymes and mitochondrial ROS generation [42,43]. These results indicated that generation of superoxide induced by DPP4 also contributed to the ER tress, hepatic lipid accumulation and insulin resistance.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, we found that silence of DPP4 inhibited superoxide generation induced by HNF1b knockdown in AML-12 hepatocytes, indicating that DPP4 also involved in HNF1b knockdown-associated superoxide generation. Previous studies have reported that DPP4 inhibitors played an antioxidant role mainly through regulating expression of antioxidant enzymes and mitochondrial ROS generation [42,43]. These results indicated that generation of superoxide induced by DPP4 also contributed to the ER tress, hepatic lipid accumulation and insulin resistance.…”
Section: Discussionmentioning
confidence: 83%
“…Third, CD26 controls energetic metabolism and energy supply to cells via degradation of peptides such as the glucagon-like peptide 1 (41). Last, but not least, a long-term loss of CD26 activity was reported to increase the capability against the oxidative stress and reactive oxygen species (38). Although addressing CD26 substrates was out of the scope of this work, monitoring them during hyperoxia certainly deserves further study.…”
Section: Discussionmentioning
confidence: 91%
“…The antiapoptotic effect of GLP-1 is PKA dependent because the improvement of cell viability of GLP-1 after H 2 O 2 exposure was blocked by H89, a PKA inhibitor (40). GLP-1 had an antiapoptotic activity mediated by a cAMP/PKA-dependent signaling pathway in ␤-cells (36) and endothelial cells (14).…”
Section: Discussionmentioning
confidence: 99%